In vitro anti-Toxoplasma gondii efficacy of synthesised benzyltriazole derivatives - Huanping Guo (Onderstepoort Journal of Veterinary Research, 2021)
Toxoplasma gondii, an obligate intracellular parasite, is the aetiological agent of toxoplasmosis, a disease that affects approximately 25% – 30% of the world’s population. At present, no safe and effective vaccine exists for the prevention of toxoplasmosis. Current treatment options for toxoplasmosis are active only against tachyzoites and may also cause bone marrow toxicity. To contribute to the global search for novel agents for the treatment of toxoplasmosis, we herein report the in vitro activities of previously synthesised benzyltriazole derivatives. The effects of these compounds against T. gondii in vitro were evaluated by using a expressing green fluorescent protein (GFP) type I strain parasite (RH-GFP) and a type II cyst-forming strain of parasite (PruΔku80Δhxgprt). The frontline antitubercular drug isoniazid, designated as Frans J. Smit -isoniazid (FJS-INH), was also included in the screening as a preliminary test in view of future repurposing of this agent. Of the compounds screened, FJS-302, FJS-303, FJS-403 and FJS-INH demonstrated 80% parasite growth inhibition with IC50 values of 5.6 µg/mL, 6.8 µg/µL, 7.0 µg/mL and 19.8 µg/mL, respectively. FJS-302, FJS-303 and FJS-403 inhibited parasite invasion and replication, whereas, sulphadiazine (SFZ), the positive control, was only effective against parasite replication. In addition, SFZ induced bradyzoite differentiation in vitro, whilst FJS-302, FJS-303 and FJS-403 did not increase the bradyzoite number. These results indicate that FJS-302, FJS-303 and FJS-403 have the potential to act as a viable source of antiparasitic therapeutic agents.